The importance of agonistic, antagonist and synergistic muscles coordination on swimming dry land training - Serra, N.; Carvalho, D. D.; Fernandes, R. J. (Trends in Sport Sciences, 2017)
The best dry land workout exercises for swimmers are those that aim to develop performance, strength and flexibility but without compromising health. As there is no "one-size-fitsall" recipe, coaches should be very cautious when choosing a dryland workout regimen. In fact, due to the swimming cyclic and continuous characteristics, overuse affects (almost) every swimmer, reinforcing the role that land workouts should have in preserving and promoting swimmers health, and not contributing to the high prevalence of shoulder, low back and knee joint injuries. As competitive swimmers of any age should avoid dry land workout mistakes (that will leave them prone to injury), we will briefly present a new trend on agonistic, antagonist and synergistic muscles coordination to be applied in strength and mobility dry land training.